OWNERSHIP TRANSFER AND SELLER’S OBLIGATIONS. LOOKING FOR UNITY IN SALE AGREEMENT REGULATION - Dan VELICU (Challenges of the Knowledge Society)
The Renaissance intelectuals, mostly Italians, considered Rome the climax of the European civilization and from this assumption it seemed self - evident that the Roman law was superior to any kind of regulation of other people in the Middle Ages. Later, for almost two centuries as a consequence, in a kind of inertia, in European civil law, Roman law has been taken as the sole model in order to elaborate modern civil codes. Main legal institutions belonging to Roman law were deeply analysed and their sense were strongly disputed in the frame of the European universities. If the Roman legal structure was considered a superior one to the Middle Ages peripheral usages, in the frame of the sale agreement and other contracts as well, it has looked normal that regulating seller’s obligations or ownership transfer to take place under the shadow of the Roman law. However, the authors of the modern civil codes have ignored the fact that Roman law had had a long evolution and sometimes contradictory or at least difficult to assess; unfortunately, they avoided that the rules designed by them will have to be analyzed beyond the perception of Roman law. This article aims to briefly highlight the evolution of Roman law in order to see if the full takeover of some of its institutions is justified today. We shall try also to point out the possible way to reconcile what now it seems to be irreconcilable in the sphere of European systems influenced by ius civile.